Effects of the novel and potent lymphocyte-specific protein tyrosine kinase inhibitor TKM0150 on mixed lymphocyte reaction and contact hypersensitivity in mice - Takayama, Tetsuo; Takaoka, Akiko; Takahashi, Shuya; Takahashi, Akiko; Umemiya, Hiroki; Sato, Masakazu (Arzneimittelforschung, 2010)
Lymphocyte-specific protein tyrosine kinase (Lck) plays a critical role in T cell activation. In the present study, the effect of a newly synthesized small molecule compound, 7-[2-(dimethylamino)ethoxy]-2-(4-phenoxyphenyl)-9,10-dihydro-4H- pyrazolo[5,1-b][1,3]benzodiazepine-3-carboxamide (TKM0150) on Lck activity was investigated. TKM0150 inhibited Lck with an IC50 value of 0.7 nM. To evaluate if TKM0150 is a specific inhibitor of Lck, the activity against several Src (Proto-oncogene tyrosine-protein kinase Src) and non-Src family kinases were assayed. TKM150 inhibited Src family kinases, Src and Csk (c-Src kinase) (with IC50 values of 0.6 nM and 1.7 nM, respectively) as well as Fyn (p59-Fyn) and Lyn (tyrosine-protein kinase Lyn) at a dose of μM; however, it did not inhibit kinase which is a non-Src family kinase in the tyrosine kinase (TK) group, nor kinases in other groups. Then, the antiinflammtory potential of TKM0150 was evaluated by known experimental models. TKM0150 inhibited the murine mixed lymphocyte reaction (MLR) in vitro with an IC50 value of 0.7 nM, and 2,4,6-trinitro-l-chlorobenzene-induced contact hypersensitivity in vivo at a dose of 0.3 and 1% w/v administered topically. These results indicate that TKM0150 is a specific inhibitor of Lck/Src kinase and can block T cell-mediated responses in vitro and in vivo. Accordingly, TKM0150 would be expected as a drug candidate for treating T cell-mediated disorders including atopic dermatitis.
Keywords: Atopic dermatitis; Contact hypersensitivity; Lymphocyte-specific protein tyrosine kinase, inhibitor; Mixed lymphocyte reaction; TKM0150